Survival of Pseudomonas syringae pv. lachrymans–incitant of angular leaf spot of cucumber under temperate conditions of Kashmir valley - BHAT*, NAZIR A. (Indian Phytopathology, 2009)
Studies on role of seed and infected crop debris in survival of Pseudomonas syringae pv. lachrymans, incitant of angular leaf spot of cucumber under temperate conditions of Kashmir valley revealed that both naturally infected and the artificially inoculated seed could harbour the pathogen for varying periods. Maximum inoculum load (9.9 X 103 ) could be retrieved from the artificially inoculated seed in the first assay conducted 2 months after its inoculation, followed by those obtained from the naturally infected fruits (5.3 X 103 ). Inoculum load on the seed declined periodically and was least at the time of last assay conducted after 21 months. Percentage of the infected seedlings obtained from the infected seed also declined with the passage of time. On diseased crop debris, the pathogen population showed a regular decline with highest population recorded soon after harvesting (cfu 7.4 x 104) and least at the last assay conducted after eight months (cfu 1.61 x 102 ). The extent of decline was greater in case of debris buried under soil than that kept on soil surface. Besides cucumber (Cucumis sativus), the pathogen infected muskmelon (C. melo), watermelon (Citrullus lanatus), pumpkin (Cucurbita moschata), squash (C. maxima), wild melon (Cucumis melo fsp. agrestis var. agrestis), bottle gourd (Lagenaria siceraria), bitter gourd (Momordica charantia Poir) and sponge gourd (Luffa acutangula) under conditions of artificial inoculation but under natural conditions the disease was recorded on all these cucurbits except bottle gourd, bitter gourd and sponge gourd.